Constraints in the Adoption of Farm Pond in Drought Regions of Maharashtra - Shivakumarappa, Gireesh; Kumbhare, N. V.; Padaria, R. N.; Burman, R. R.; Kumar, Pramod; Bhoumik, Arpan; Prasad, Shiv (Indian Journal of Extension Education, 2022)
During 2021-22, the beneficiaries and non-beneficiaries of the farm pond on-demand initiative in Maharashtra’s Vidarbha and Marathwada regions were analysed and identified the constraints associated with farm pond adoption. Through focus group discussions, observations, and semi-structured interviews with 160 beneficiaries and 160 non beneficiaries of the farm pond programme, quantitative and qualitative data were gathered. The adoption and discontinuation of agricultural ponds were analysed using the rank-based quotient (RBQ) approach to find barriers and contributing variables. After consulting with subject matter experts, reading pertinent literature, and having a conversation with respondents, a list of constraints divided into four major categories-technical, economic, ecological, and personal constraints-and the perceived significant reason for the discontinuation of the farm pond was noted. Results revealed that the economic constraints were considered the most serious ones, with a mean RBQ value of 88.85. Followed by technological (78.25), ecological (61.82) and personal constraints (58.18). Draining the bore well or well to store water in the farm pond was considered as the most serious perceived reason to discontinue the farm pond with an RBQ value of 44.94, followed by a less productive period of farm pond reported by the respondents with RBQ values 40.38.
Keywords: Farm pond; Beneficiary; Non beneficiary; Vidarbha; Marathwada; Constraints; Rank Based Quotient (RBQ)